1995
DOI: 10.1161/01.cir.92.10.3051
|View full text |Cite
|
Sign up to set email alerts
|

The Ib Phase of Ventricular Arrhythmias in Ischemic In Situ Porcine Heart Is Related to Changes in Cell-to-Cell Electrical Coupling

Abstract: In the regionally ischemic in situ porcine heart, loss of cell-to-cell electrical interaction is related to the occurrence of VF and changes in the amplitude of the injury current. Cellular electrical uncoupling contributes to failure of impulse propagation in the setting of altered tissue excitability as a result of elevated [K+]e and low pHe. These data indicate that Ib arrhythmias and ECG changes during ischemia are influenced by the loss of cell-to-cell electrical interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
137
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(161 citation statements)
references
References 49 publications
16
137
0
7
Order By: Relevance
“…One other possibility is a direct electrophysiological eect of NO generated from NCX4016, although the evidence surrounding this property of NO remains controversial (Pabla & Curtis, 1995;Barnes & Coker, 1995). Furthermore, the observation that both phase 1a and 1b arrhythmias were attenuated by NCX4016 would argue against this, since there is some evidence that dierent electrophysiological mechanisms underlie these two phases of arrhythmias in the porcine heart (Smith et al, 1995).…”
Section: +4* 187+13{mentioning
confidence: 99%
“…One other possibility is a direct electrophysiological eect of NO generated from NCX4016, although the evidence surrounding this property of NO remains controversial (Pabla & Curtis, 1995;Barnes & Coker, 1995). Furthermore, the observation that both phase 1a and 1b arrhythmias were attenuated by NCX4016 would argue against this, since there is some evidence that dierent electrophysiological mechanisms underlie these two phases of arrhythmias in the porcine heart (Smith et al, 1995).…”
Section: +4* 187+13{mentioning
confidence: 99%
“…Experiments have shown that ischemia 1B ventricular fibrillation is based on reentry around fixed lines of block, which are thought to arise from heterogeneous subepicardial electrical uncoupling in the central ischemic zone (CIZ). 2,10 We hypothesize that heterogeneous uncoupling between depressed depolarized midmyocardium and the surviving subepicardium in ischemia phase 1B results in heterogeneous refractoriness in the subepicardium and that this dispersion in effective refractory period (ERP) contributes to the substrate for reentrant arrhythmias in ischemia phase 1B. Furthermore, we investigate how vulnerability to reentrant arrhythmias is affected by the degree of heterogeneous uncoupling between subepicardial and midmyocardial layers as well as by the degree of depolarization in the inactive midmyocardial layer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that reduced expression of Cx43 results in a significant reduction in conduction velocity during acute MI and accelerates the onset and increases the incidence of ischemia-induced ventricular arrhythmias (2,3,(8)(9)(10). These results suggest that the changes in Cx43 expression may play a significant role in the genesis of ventricular arrhythmias during acute MI.…”
Section: Discussionmentioning
confidence: 72%